2010
DOI: 10.1185/03007995.2010.542081
|View full text |Cite
|
Sign up to set email alerts
|

Study comparing the effect of pioglitazone in combination with either metformin or sulphonylureas on lipid profile and glycaemic control in patients with type 2 diabetes (ECLA)

Abstract: Since improvement of both glycaemic control and lipid profile are considered main targets in the management of the diabetic patient, the results of the present study, conducted under conditions of everyday clinical practice, show that pioglitazone may be considered a potential choice for the treatment of type 2 diabetes, when lifestyle and metformin fail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…Our study was consistent with others [25][28] and showed that acarbose and metformin treatment causes a slight decline of plasma TC and non-HDL-C in the three BMI groups. Acarbose decreased TG more intensively as compared with metformin in overweight and obesity groups.…”
Section: Discussionsupporting
confidence: 93%
“…Our study was consistent with others [25][28] and showed that acarbose and metformin treatment causes a slight decline of plasma TC and non-HDL-C in the three BMI groups. Acarbose decreased TG more intensively as compared with metformin in overweight and obesity groups.…”
Section: Discussionsupporting
confidence: 93%
“…Previous reports revealed that acarbose and metformin both had some beneficial effects on metabolic syndrome. Our finding was consistent with others [29][30][31][32] and revealed that acarbose and metformin could decrease plasma TC and non-HDL-C slightly in the three groups. The proportion of patients with optimal LDL-C levels with metformin treatment was higher than acarbose in better β-cell function group.…”
Section: Discussionsupporting
confidence: 93%
“…Metformin exhibited antidiabetic activity in terms of reducing glucose as well as triglyceride in the rats exposed to both T2DM and stress paradigm. Metformin decreases T2DM-induced increase in the level of glucose and triglyceride in the plasma of both animals and patients [62, 63]. However, this is the first report of effect of metformin on the rats exposed to both T2DM and stress paradigm.…”
Section: Discussionmentioning
confidence: 99%